Types of mergers and acquisitions of companies as an element of business activity in the process of integration (Путеводитель предпринимателя)
The article discusses various types ofassociation, mergers and acquisitions as an important process of business development at present. The characteristics of the basic concepts of the integration of companies in the process of integration.